The role of the eae gene of enterohemorrhagic Escherichia coli in intimate attachment in vitro and in a porcine model. - Donnenberg, M S (1993)
The eaeA gene of enteropathogenic Escherichia coli (EPEC) is necessary for intimate attachment to epithelial cells in vitro. Enterohemorrhagic E. coli (EHEC) strains also possess an eae gene and are capable of intimate attachment and microvillus effacement in vitro and in animal models. To assess the role of the EHEC eae gene in intimate attachment, we constructed an eae deletion/insertion mutation in wild-type EHEC O157:H7 strain 86-24 by using linear electroporation of a recombinant allele. The mutant obtained was deficient in inducing f-actin accumulation in HEp-2 cells and was incapable of attaching intimately to colonic epithelial cells in a newborn piglet model of infection. Intimate attachment in vivo was restored when the EHEC eae gene or the eaeA gene of EPEC was introduced into the mutant on a plasmid. These results indicate that the eae gene is necessary for intimate attachment of EHEC in vivo. In addition, the complementation achieved by the EPEC locus indicates that the eae gene of EHEC and the eaeA gene of EPEC are functionally homologous.